Strategy Forming Hard Skills and Soft Skills Teaching Factory at SMK Warga Surakarta - Valiant Lukad Perdana Sutrisno (International Journal Labs, 2025)
Vocational education plays a strategic role in preparing competent human resources aligned with labor market demands. One approach is forming hard skills and soft skills through the implementation of Teaching Factory (TEFA). This study aims to explore the formation of these skills at TEFA SMK Warga Surakarta and identify factors affecting its success. Using a qualitative descriptive case study method, data were collected through purposive and snowball sampling with interviews, observations, and document analysis. The results show that hard skills are developed by having students operate machines and master design software. Students also learn to plan tasks, use measuring instruments, and consistently apply the 5R work culture. Soft skills develop through leadership practice, teamwork, direct communication with consumers, and public speaking during learning sessions. Additionally, students manage orders, take responsibility for supervising work, and adapt to various roles. Teachers act as instructors by providing competencies and creating tasks for students, while also assisting them during work. The industry partners supply practical jobs and evaluate student outcomes to ensure learning aligns with industry standards. This integrated approach at TEFA SMK Warga Surakarta effectively combines technical and interpersonal skills, preparing students for real-world challenges and enhancing their readiness for future employment.